Acute chest pain in an adolescent with cystic fibrosis in September: Would you have thought about this?. Issue 10 (31st May 2017) - Dowaikh, Hiba; Morfin‐Sherpa, Florence; Reix, Philippe
Abstract : Acute chest pain is common in patients with cystic fibrosis (CF). Here we report the case of an adolescent who suffered acute chest pain in September after an history of acute abdominal pain and fever. The reason for this clinical sceneriao was found to be Coxsackievirus B3, known to be responsible of Bornholm disease, a frequent but under recognized viral myositis. The diagnosis is mainly clinical, but evocating this diagnosis may avoid unnecessary exam.